Health Outcomes in a Foreign Land : A Role for Epigenomic and Environmental Interaction - Kwabi-Addo, Bernard (Springer International Publishing : Imprint: Springer, 2017)
This stimulating volume uses multiple lenses to analyze the complex causes of health disparities affecting minorities, in particular African Americans, and explains how this knowledge can be used to reduce their destructive effects. Pinpointing genetic, non-genetic, and epigenetic factors underlying health conditions common to the population-including heart disease, hypertension, diabetes, and cancer-the author traces intricate links among these factors in the current environmental and social context. The section on non-genetic factors in health disparities, such as social determinants and health behaviors, adds depth to the ongoing discourse on public health and health policy objectives. And the chapters on gene/environment interactions outline the vast potential for developing new multidisciplinary frontiers in shrinking health inequities and personalizing care. Included in the coverage: The African diaspora and disease-specific disparities The genetic basis to health disparities The role of epigenetics Economic factors and health Psychological issues and how they affect disparities Gene-environment interactions in health disparities Race, a biological or social concept Compelling and accessible, Health Outcomes in a Foreign Land will challenge and inspire medical students, epidemiologists, public health professionals, biomedical research scientists, and social scientists to go farther in their work. A wider audience would include policymakers, government officials, nurses, physicians, lawyers, economists, community outreach investigators, and interested general readers. .
Keywords: Medicine.; Human genetics.; Epidemiology.; Social structure.; Social inequality.; Ethnicity.; elektronické knihy; electronic books